2013
DOI: 10.4103/0019-557x.115006
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal status among tobacco users in Karnataka, India

Abstract: A cross-sectional study was designed to assess the prevalence of periodontal diseases among tobacco and non-tobacco users. A total of 2,156 dentate subjects were selected in the age group of 35-44 years through multi-stage sampling method. A total of 350 and 175 subjects were selected from household survey from each district in rural and urban areas. Subjects were interviewed for the tobacco usage status, followed by clinical assessment of periodontal status. Prevalence of calculus, periodontal pockets of 4-5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 0 publications
3
10
0
Order By: Relevance
“…Thus, we conclude that the previous and current use of shammah plays an analogous role in the disappearance of periodontal disease once the shammah use is stopped. Our findings are similar to those of previous studies that report a significant association between periodontal disease and tobacco use [ 18 , 34 , 35 ]. Kumar et al [ 36 ] examined 513 dentate adult males to determine the effect of tobacco use on the severity of periodontal disease in India.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, we conclude that the previous and current use of shammah plays an analogous role in the disappearance of periodontal disease once the shammah use is stopped. Our findings are similar to those of previous studies that report a significant association between periodontal disease and tobacco use [ 18 , 34 , 35 ]. Kumar et al [ 36 ] examined 513 dentate adult males to determine the effect of tobacco use on the severity of periodontal disease in India.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, majority were males in the smokers and smokeless tobacco users groups, which is in agreement with the studies conducted by Rooban et al and Mohamed and Janakiram20,21. But conversely, a study by Lashkari and Shukla on smokeless tobacco users in Karnataka, India showed that females were about half of the study population (45.9%)18.…”
Section: Discussionsupporting
confidence: 92%
“…[20] Widespread tobacco smoking has been reported in previous surveys in India. [112122] Our survey revealed that 67.6% of the brick kiln workers were smokers and out of them 96.7% of those who smoked 6–10 cigarettes/beedis per day had periodontal disease.…”
Section: Discussionmentioning
confidence: 92%